The effect of sport drinks on muscle endurance performance among football athletes / Hazwan Adli Hamadan - Hamadan, Hazwan Adli (Faculty of Sports Science and Recreation, 2018)
The purpose of this study was to identify the effect of sport drink consumption on muscle endurance performance among football athletes. A total of 20 football athletes (N=20) was selected via purposive sampling to participate in this study. In this study, push up until fatigue protocol were been used for pre-test and post-test (Magrini, Colquhoun, Dawes, & Smith, 2016). In this study, athletes were consuming sport drinks and placebo drink. This study using cross sectional design and quasi experimental for pre-test and post-test. Paired Sample T-test was employed to compare means and standard deviation between two variables which is sport drink and placebo drinks. The analysis showed there were significant different on sport drinks and placebo drinks on muscle endurance performance among football athletes, which is sport drink t (9) = -7.749, P <.05 and placebo drinks t (9) =- 9.327, P <.05. At the conclusion, sport drinks and placebo have effects on muscle endurance performance among football athletes in their respective responses